Fischer 344 Rat. Issue 7 (September 2015) - Azaïs, Henri; Queniat, Gurvan; Bonner, Caroline; Kerdraon, Olivier; Tardivel, Meryem; Jetpisbayeva, Gulim; Frochot, Céline; Betrouni, Nacim; Collinet, Pierre; Mordon, Serge
<x xml:space="preserve">Abstract</x> Objective Ovarian cancer prognosis remains dire after primary therapy. Recurrence rates are disappointingly high as 60% of women with advanced epithelial ovarian cancer considered in remission will develop recurrent disease within 5 years. Special attention to undetected peritoneal metastasis and residual tumorous cells during surgery is necessary as they are the main predictive factors of recurrences. Folate receptor α (FRα) shows promising prospects in targeting ovarian cancerous cells. Our aim was to determine if the Fischer model described by Rose et al could be used to evaluate folate-targeted therapies in preclinical studies. Methods NuTu-19 epithelial ovarian cancer cell line was used to induce peritoneal carcinomatosis in female Fischer 344 rats. FRα expression by NuTu-19 cells was assessed in vitro by immunofluorescence using "Cytospin®" protocol. In vitro folate-targeted compound uptake by NuTu-19 cells was evaluated by incubation of FRα-positive ovarian cancer cell lines (NuTu-19/SKOV-3/OVCAR-3/IGROV-1) with or without (control) a folate-targeted photosensitizer. Intracellular incorporation was assessed by confocal microscopy. Determination of in vivo FRα tissue expression by several organs of the peritoneal cavity was studied by immunohistochemistry. Results NuTu-19 cells express FRα which allows intracellular incorporation of folate-targeted compound by endocytosis. FRα is expressed in tumor tissue, ovary, and liver. Peritoneum, colon, small intestine, and kidney do not express the receptor. Conclusions Female Fischer 344 rat is an inexpensive reproducible and efficient preclinical model to study ovarian peritoneal carcinomatosis folate-targeted therapies.